The influence of exogenous factors on risk perception amongst insurance policyholders - Yvonne Makalani; Suné Ferreira-Schenk; Zandri Dickason-Koekemoer (Cogent Business & Management, 2022)
Insurers tend to misunderstand the perceptions of the policyholders and inevitably lose clients. In South Africa, very little research has investigated the perceptions and attitudes expressed by insurance policyholders. Therefore, to bridge this gap, the purpose of this research study is to analyse the exogenous factors that influence the risk perception of insurance policyholders in Gauteng. This will inevitably assist insurers to retain more clients as they will have a better understanding of what influences the risk perception of their insurance policyholders. Exogenous factors relate to external factors influencing the risk perception of insurance policyholders namely, political-legal, market fluctuations, crime and unemployment. The questionnaire was distributed to private insurance policyholders in Gauteng, South Africa. Political events and market fluctuations and volatility had significant relationships with the risk perception of policyholders. It can be assumed that the more market volatility exists, or extreme international events take place the more the level of perceived risk by the insurer will be. In terms of demographics, there were also significant relationships between age, level of education, policy type and gender and risk perception. The empirical findings of this research study will furthermore be of benefit to the insurance industry as it provides an analysis of the exogenous factors influencing the risk perception of the insurance policyholders. This can assist insurers to tailor insurance products accordingly for each policyholder in order to maximise customer satisfaction, especially in unprecedented market conditions.
Keywords: E24; G22; J10; 650; risk perception; unemployment; crime; demographics; insurance; political-legal